Construction de l’événement médiatique à l’exemple de la crise des migrants en Europe. Vers une dimension argumentative - Dyoniziak, Jolanta (Studia Romanica Posnaniensia, 2017)
In this publication we would like to consider the issue of discursive strategy responsible for mediatisation of the migrant crisis currently taking place in Europe, partly as a result of military actions in the Middle East. The first objective is to describe media representation of the European migrant crisis published in the French and Polish press over the last five years. The author especially emphasizes one discursive moment, year 2015, when a significant increase in the number of migrants arriving in Europe occurred. The next task will be to assess the argumentative potential that results from a particular staging of the discussed event.